On the ultimate and governing motif of the Critique of Pure Reason - Bonaccini, Juan Adolfo (Estudios de Filosofía, 1996)
Contrary to the standard point of view when studying the Critique of Pure Reason, the author does not consider as its foundation the question of knowledge but the question of Metaphysics. Metaphysics produces antinomies, and if Pure Reason limits itself to the Sufficient Reason, it falls into a conflict of laws. According to this view, the Transcendental Dialectics, and more preciselly the antinomies within it, are the core of Kant’s intention of realizing the destiny of philosophy by means of Metaphysics.